INNOVATIONS AS A CATALYST FOR CHANGE IN HOSPITALITY EDUCATION AND SUSTAINABLE DEVELOPMENT PRACTICES - Будник, Ніна; Мороз, Світлана; Калашник, Олена (Modern engineering and innovative technologies, 2025)
The article examines the role of innovation as a catalyst for change in education and the practice of sustainable development within the hotel industry. It analyzes current trends in the implementation of environmentally oriented technologies, digital sol